The Representation of Science and Scientists on Stamps - B. Yardley, Christopher (ANU Press, 2015)
The Representation of Science and Scientists on Postage Stamps examines how the postal authorities of the world have developed unique techniques to portray science and scientists in order to convey a message behind the stamp issue. It is a multi-disciplinary examination that investigates visual representation, semiotics, science, science history and politics, amongst other issues. The author introduces and describes a technique for looking at how and why images may have been chosen. Is the image a mirror reflecting a known reality or is it a lens to challenge, to prompt further thought or action? He also hypothesises that the Internet created a real change to science communication, influencing the way images of science were used. The stamp message changed from that of pursuing a public understanding approach to an awareness of science with its increasing contextual content.